Translation of Adjectival Collocations in Sidney Sheldon’s “Tell Me Your Dreams” into Indonesian - Johannes E. Joseph (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2022)
Translating collocation is one of the most challenging tasks due to the linguistic and semantic features they have. This study analyzes the translation of the adjectival collocations of “Tell me your Dreams” into Indonesian. To be more specific, it aims at (1) discovering how English adjectival collocations are translated into Indonesian; (2) figuring out how many types of equivalence there are in the Indonesian translation from the English adjectival collocations; (3) discovering how many types of shift there are in the Indonesian translation from the English adjectival collocations; (4) figuring out whether shift happens more than equivalence or vice versa; and (5) figuring out whether the collocation translation makes the TL cohesive and coherent or not. This study uses a qualitative descriptive method because all of the data that are analyzed in this research are in form of words and sentences not numbers and it is directed to answer research questions concerning the status of the subject of the study. The result shows that equivalence dominates the translation of English collocations into Indonesian in the novel with 30 (58.8%) of the whole data, and the amount of shift is 21 (41.2%) of the whole data.